Reliability and Validity Study of Turkish Version of Pediatric Eosinophilic Esophagitis Symptom Scores® (Tr-PEESS v2.0) Led to Development of a New Pediatric Eosinophilic Esophagitis Scale: GaziESAS - Ertoy Karagöl, Hacer İlbilge; Yapar, Dilek; Eğritaş Gürkan, Ödül; Sarı, Sinan; İlhan, Mustafa Necmi; Dalgıç, Buket; Bakırtaş, Arzu; Pediatric Eosinophilic Gastrointestinal Diseases Working Group, Gazi University (Turkish Journal of Gastroenterology, 2021)
Background/Aims: There has been no valid and reliable Turkish scale that measures symptoms in children with eosinohilic esophagitis (EoE). The aim of the study is test the validity and reliability of Turkish version of Pediatric Eosinophilic Esophagitis Symptom Scores® (Tr-PEESS v2.0)Materials and Methods: Relevant forms of Tr-PEESS v2.0 were applied to 2-18 years old children with EoE and to their parents. KINDL QoL patient and parent questionnaires and GaziESAS scale which was developed in this study were used to test convergent validity of Tr-PEESS v2.0. Discriminant validity was evaluated among three EoE treatment groups: under treatment, off treatment due to remission and uncompliant with treatment. Reliability was evaluated by internal consistency, test-retest reliability, and item analysis.Results: Fiftytwo children/teens (mean age 130.2±60.3 months) and 84 parents were interviewed twice one week apart. Mean duration of EoE was 47.2±35.6 months. Tr-PEESS v2.0 reports correlated with GaziESAS (range,0.361-0.855) and KINDL QoL questionnaires (range,-0.316-0.413). Parent report of Tr-PESS v2.0 discriminated children uncompliant with treatment from the ones off treatment and undertreatment. Cronbach’s α values and intraclass correlation coeffcients (ICC) values of Tr-PEESS v2.0 ranged from 0.614 to 0. 895 and 0.646 to 0.910, respectively.Conclusion: Tr-PEESS v2.0 is a valid and reliable tool to use in Turkish children. GaziESAS is a new parent-proxy pediatric EoE scale with additional adaptive behaviour domain that passed scale developmental stages successfully for Turkish children with EoE.